The EFFECTIVENESS OF VIRTUAL REALITY BASED EXERCISES ON UPPER EXTREMITY FUNCTIONAL ABILITY AND COGNITIVE FUNCTION FOR PATIENTS WITH STROKE - Ilham Fatria (Jurnal Inovasi Pendidikan dan Sains, 2022)
The objective of this study is to determine the effectiveness of Virtual Reality (VR) based exercises on upper extremity functional ability and cognitive functions in patients with stroke. This research is quasi-experiment using a pre–post test randomized control design. The treatment group I consisted of 8 people who were given conventional exercise, while in the treatment group II there were 8 people who were given VR-based exercises. This research was conducted at the Sri Mulyani Physiotherapy Clinic for 4 weeks from October to November 2022. The instrument for measuring upper extremity functional ability used the Wolf Motor Function Test (WMFT) and the instrument for measuring cognitive function used the Montreal Cognitive Assessment (MoCA-INA). The study showed that the upper extremity functional ability using WMFT showed that the results of the treatment group I showed an insignificant increase on upper extremity functional ability (p>0.05 or p=0.0520) and the results of the treatment group II showed an significant increase on upper extremity functional ability (p>0.05 or p=0.0003***). The measurement of cognitive function using the MoCA-INA showed that the results of treatment group I showed a slightly insignificant increase in cognitive function (p> 0.05 or p=0.4439) and treatment group II showed a significant increase in cognitive function (p>0.05 or p=0.0014**). The conclusions of this study indicate that conventional exercises and VR-based exercises can improve both upper extremity functional ability and cognitive function in post-stroke individuals. However, statistically, it appears that VR-based exercises are more effective. Keywords : Stroke, Upper Extremitty Function Ability, Cognitive Function, Conventional Exercise, Virtual Reality Based Exercise